2018
DOI: 10.1177/2041669518767171
|View full text |Cite
|
Sign up to set email alerts
|

Colour for Behavioural Success

Abstract: Colour information not only helps sustain the survival of animal species by guiding sexual selection and foraging behaviour but also is an important factor in the cultural and technological development of our own species. This is illustrated by examples from the visual arts and from state-of-the-art imaging technology, where the strategic use of colour has become a powerful tool for guiding the planning and execution of interventional procedures. The functional role of colour information in terms of its potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 154 publications
0
10
0
Order By: Relevance
“…It is shown that stronger contrasts combined with higher sound frequencies led to faster perceptual decisions [17,18]. This facilitating effect of sound frequency on response times for "nearer" was consistently stronger in the positively signed, light-on-dark, contrast configurations, as predicted by functional asymmetries between the "on" and "off" contrast processing channels of the visual brain [19][20][21][22][23][24][25][26][27][30][31][32]. Moreover, as the number of contrast elements in the 2D patterns increased, the effect of sound on response times also increased statistically, regardless of the contrast sign of the patterns, as predicted by spatial probability summation in the "on" and "off" contrast processing channels of the visual brain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is shown that stronger contrasts combined with higher sound frequencies led to faster perceptual decisions [17,18]. This facilitating effect of sound frequency on response times for "nearer" was consistently stronger in the positively signed, light-on-dark, contrast configurations, as predicted by functional asymmetries between the "on" and "off" contrast processing channels of the visual brain [19][20][21][22][23][24][25][26][27][30][31][32]. Moreover, as the number of contrast elements in the 2D patterns increased, the effect of sound on response times also increased statistically, regardless of the contrast sign of the patterns, as predicted by spatial probability summation in the "on" and "off" contrast processing channels of the visual brain.…”
Section: Discussionmentioning
confidence: 99%
“…Positively signed light-on-dark pattern pairs (Figure 3, graphs on left) produced shorter response times in comparison with negatively signed dark-on-light pattern pairs (Figure 3, graphs on right), despite the fact that the pattern pairs with negative contrast sign displayed moderately stronger differences in visual contrast (dC) between patterns in a pair. This effect of contrast polarity was statistically significant (Table 2), which is explained by the well-documented functional asymmetry between the so-called "on" and "off" contrast processing channels in the human brain [19][20][21][22][23][24][25][26][27][30][31][32]. One of the perceptual consequences of this functional asymmetry is that positively signed contrast configurations, processed by the "on" channels of the visual brain, produce stronger effects of figure-ground segregation [24] and relative depth [17], with shorter perceptual decision times, as confirmed by results here.…”
Section: Contrast Polaritymentioning
confidence: 99%
See 3 more Smart Citations